2017
DOI: 10.3390/pathogens6010011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the KSHV Transcriptome Following Primary Infection of Blood and Lymphatic Endothelial Cells

Abstract: The transcriptome of the Kaposi’s sarcoma-associated herpesvirus (KSHV/HHV8) after primary latent infection of human blood (BEC), lymphatic (LEC) and immortalized (TIME) endothelial cells was analyzed using RNAseq, and compared to long-term latency in BCBL-1 lymphoma cells. Naturally expressed transcripts were obtained without artificial induction, and a comprehensive annotation of the KSHV genome was determined. A set of unique coding sequence (UCDS) features and a process to resolve overlapping transcripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 81 publications
(119 reference statements)
5
65
0
Order By: Relevance
“…Altering the growth conditions to allow cell migration and proliferation resulted in a substantial increase in the number of cells that were permissive for lytic infection. Similarly, within the background of many endothelial cells with long-term latent infections, spontaneous reactivation is observed in a small number of cells resulting in ORF59 expression (28,113) and virus replication (82). We have shown that this reactivation is characterized by coexpression of nuclear ORF59 and cytoplasmic LANA.…”
Section: Discussionmentioning
confidence: 99%
“…Altering the growth conditions to allow cell migration and proliferation resulted in a substantial increase in the number of cells that were permissive for lytic infection. Similarly, within the background of many endothelial cells with long-term latent infections, spontaneous reactivation is observed in a small number of cells resulting in ORF59 expression (28,113) and virus replication (82). We have shown that this reactivation is characterized by coexpression of nuclear ORF59 and cytoplasmic LANA.…”
Section: Discussionmentioning
confidence: 99%
“…Herpesviruses are adept viral pathogens that have co-evolved with their hosts over millions of years. Like all viruses their success is predicated on repurposing of the host transcriptional and translational machinery 1, 2 and through use of compact, gene-dense genomes with exceptional coding potential 37 . The 152 kb double-stranded DNA genome of herpes simplex virus type 1 (HSV-1) includes roughly 80 genes, predominantly single exon open reading frames (ORFs), some transcribed as polycistronic mRNAs, along with a smaller number non-coding RNAs 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Just as NGS technologies are revolutionizing other fields, including molecular epidemiology, pathogen surveillance, and cancer biology, it is incumbent on the wider virology research community to embrace the most recent viral genome annotation/ reannotation projects (58)(59)(60)(61) and, most importantly, to incorporate the findings of new transcriptional profiling work into ongoing studies.…”
Section: Where We Are and Where We Are Goingmentioning
confidence: 99%